Bibliometric Analysis of 20 years of Traditional Music Research in Asia - Larasati, Yuniar Galuh; Fernando, Henky; Abdullah, Irwan; Harpawati, Tatik; Morin, Leanne (Resital: Jurnal Seni Pertunjukan, 2024)
This study aims to explore and evaluate research on traditional music in Asia over the past 20 years based on a Scopus database search. This study adopts a qualitative descriptive approach using bibliometric analysis with VOSviewer software to examine and assess patterns, trends, and developments in studies on traditional music through Scopus-indexed publications. From an analysis of 1,872 documents in the Scopus database, the Asian-European Music Research Journal emerged as the most consistent source publishing studies on traditional music. The subject area of Social Sciences appeared most frequently and was the most commonly used category in studies on traditional music in Asia over the past two decades. However, these studies have remained to fully interpret and respond to the aesthetic and ethical transformations of traditional music in the era of globalization, which still has the potential to raise various issues related to culture, musical instruments, performance styles, and social functions. This study is significant for future research on traditional music, serving as a foundation for scholarly discussions in addressing the factors and implications of aesthetic and ethical transformations in traditional music in the globalized era.